Estudo de propriedades morfológicas, eletrônicas e de magneto transporte em grafeno depositado sobre talco, nitreto de boro e dióxido de silício - Edrian Mania (2015)
Graphene is a two dimensional material composed by carbon atoms arranged in a honeycomb lattice. During the past decade, it has attracted enormous interest due to the relativistic Dirac nature of its charge carriers and its potential for industrial application. For instance, charge carriers in graphene can move for distances over a micrometer without being scattered, and the electronic properties of graphenes with more than one layer are electronically tunable. However, achieve the intrinsic physical properties of graphene is challenging. Charge scattering and surface imperfection at non-flat substrates strongly affect electronic transport of graphene obscuring its intrinsic properties. In this work we investigate electronic properties of graphene devices on silicon substrates and on top of flat substrates like hexagonal boron nitride and talc. Hexagonal boron nitride shows the cleanest charge environment for graphene devices while devices on talc show instability and charge hysteresis which are still not understood. We show analyses based on optical microscopy, atomic force microscope, electronic measurement and magneto transport of graphene devices on these three substrates.